Leaders’ meetings: facilitating or replacing the formal processes in the Western Balkan countries? - Vjollca Krasniqi, Nenad Markovikj, Ilina Mangova, Enriketa Papa-Pandelejmoni and Jovan Bliznakovski (H2020 project “Closing the Gap between formal and informal institutions in the Balkan”, 2018)
The political systems of unconsolidated democracies in South Eastern Europe, more specifically, the four countries under research here, Albania, Bosnia and Herzegovina, Kosovo, and Macedonia, have produced an informal institution in political decision-making known as leaders’ meetings. Formal parliamentary political institutions and processes have often been incapacitated by boycotts, blockades, rejections from political actors who have shown how the “political rules of the game” may turn into a political conflict. In turn, the political conflicts have created and/or exacerbated the political crises, rendering the formal institutions dysfunctional, and opening a space for interventions by external actors e.g. the “international community.” The stalemates in the political decision-making and the fragility of formal political institutions have led way to the informal mechanism termed as the “leaders’ meetings,” in which substantive political disputes are resolved in private meetings between party leaders circumventing legislative and other decision-making institutions.
Keywords: leaders' meetings, EU, informality, Kosovo, Macedonia, Bosnia and Herzegovina, Albania